In Arabian nights : A caravan of Moroccan dreams - Shah, Tahir (New York ; Bantam Dell, 2009)
In this entertaining jewel of a book, Tahir Shah sets off across Morocco on a bold new adventure worthy of the mythical Arabian Nights. As he wends his way through the labyrinthine medinas of Fez and Marrakech, traverses the Sahara sands, and samples the hospitality of ordinary Moroccans, Tahir collects a dazzling treasury of traditional wisdom stories, gleaned from the heritage of A Thousand and One Nights, which open the doors to layers of culture most visitors hardly realize exist. From master masons who labor only at night to Sufi wise men who write for soap operas, In Arabian Nights takes us on an unforgettable, offbeat, and utterly enchanted journey.
Keywords: SHAH, TAHIR; TRAVEL WRITERS -- MOROCCO -- BIOGRAPHY; MOROCCO -- DESCRIPTION AND TRAVEL